A case of rectus sheath haematoma related to severe coughing in a patient with acute exacerbation of chronic obstructive pulmonary disease. Issue 6 (November 2019) - Wong, Ching Hin Kevin; Tsang, Ho Kai Patrick; Wong, Oi Fung; Ma, Hing Man; Lit, Chau Hung Albert
Introduction: Rectus sheath haematoma is a rare condition which is often misdiagnosed. Apart from abdominal trauma and anticoagulation, severe coughing is an uncommon precipitating cause of this rare condition. Case presentation: An elderly gentleman with history of ischaemic heart disease on aspirin developed rectus sheath haematoma due to severe coughing during an episode of acute exacerbation of chronic obstructive pulmonary disease. He developed severe abdominal pain and was noted to have epigastric bruising extending to bilateral loins. Ultrasound abdomen and computed tomography of the abdomen with contrast revealed haematoma over bilateral upper rectus abdominis muscles, which subsided with conservative management. Discussion and conclusion: Rectus sheath haematoma can be related to severe coughing. In patients, especially those with predisposing factors, presenting with abdominal pain and palpable painful abdominal mass, clinicians should raise the suspicion of this uncommon cause so that timely and appropriate management can be provided.